Micro-manufacturing technology: the huge opportunity of thinking small - Ali, Mohammad Yeakub (2011)
Recently there is a rapid growth in micro-manufacturing technology especially in the areas of biomedical, electronics, automotive, and military applications. In micro-manufacturing, the dimension of the part range from few micrometers to few millimeters with sub-micrometer accuracy and nano-metric surface finish. It requires new and at least modified mathematical models in cutting and forming operations of miniaturized products. The motivation of miniaturization and micro-manufacturing come from numerous advantages of micro device and systems (MEMS) such as less power consumption, high speed, greater density, economy, etc. This presentation will cover various micro-manufacturing technology especially silicon micromachining and toll based micro manufacturing (M4) techniques such as micro milling, micro electro discharge machining, etc. In addition, modification of existing machine tools for micro manufacturing will be highlighted for cost reduction and to open the doors for all researchers.